On limit theorems in JW-Algebras - Karimov , Abdusalom; Mukhamedov, Farrukh (Kazimierz Urbanik Center for Probability and Mathematical Statistics, 2010)
In the present paper, we study bundle convergence in JW- algebra and prove certain ergodic theorems with respect to such convergence.Moreover, conditional expectations of reversible JW-algebras are considered. Using such expectations, the convergence of supermartingales is established.